Penentuan Daerah Prospek Mineralisasi Logam Dasar Cu-Pb-Zn dengan Analisis Faktor pada Eksplorasi Geokimia Stream Sediment. - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Magister Manajemen UGM, 2001)
The objective of the this reserch is so determine the prospect area of base metal (Cu-Pb-Zn) mineralization using factor analysis.The investigation area involves of pasang kayu-Poso map sheet, central Sulawesi, geologycally, this area lies within the magmatic zone of western Sulawesi Province, which is base metalminaralization-bearing.By using strim sediment geochemical method has been collected 1138 sample with density of 10-15 samples/km2.After preparetion then the samples were analysed using AAS(automatic absorption spectrophotometry) and visual colometry for 11 elements(Cu,Pb,Zn,Co,Ni,Mn,Ag,Li,K,Fe and Cr).The data processing of multivariate method using factor analysis indficatesthe base metal(Cu-Pb-Zn)mineralization can be localized on five prospect areas they are Pasangkayu, Tomoa, Karangana1, Karangana2 and Bengahulu.Those areas are recomended to semi datail geochemical exploration.